2014
DOI: 10.3945/ajcn.113.081554
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose compared with artificial sweeteners: a clinical intervention study of effects on energy intake, appetite, and energy expenditure after 10 wk of supplementation in overweight subjects

Abstract: The changes in body weight in the 2 groups during the 10-wk intervention seem to be attributable to changes in EI rather than to changes in EE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 34 publications
1
55
0
Order By: Relevance
“…Overall, these studies have reported neutral effects or modest benefits of LCS on energy intake [43, 44] and weight [21, 22, 27, 28, 30, 31, 4547]. For example, de Ruyter et al [21] reported less weight gain in children assigned to replace their daily sugar-sweetened beverage with a flavor-matched non-caloric beverage in an 18-month intervention.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, these studies have reported neutral effects or modest benefits of LCS on energy intake [43, 44] and weight [21, 22, 27, 28, 30, 31, 4547]. For example, de Ruyter et al [21] reported less weight gain in children assigned to replace their daily sugar-sweetened beverage with a flavor-matched non-caloric beverage in an 18-month intervention.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Reductions in body weight following replacement of sugar-sweetened beverages with LCS, particularly when studied in the context of weight loss (see Section 2.7. ), are convincing; yet, many of these studies lack a true control [21, 22, 30, 44, 45, 4749]: that is, plain water, unsweetened seltzer, and/or calorie-matched foods without sweetness.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…~ 1 liter/day) to their diets for periods of 6 – 10 weeks, outcomes are significantly worse when the beverages are sugar-sweetened compared to artificially-sweetened [e.g. [18]. However, data from other interventional studies indicate that weight loss outcomes are similar when sugar-sweetened beverages were replaced by either water or artificially sweetened beverages [19], and that consuming artificially-sweetened beverages in place of sugar-sweetened beverages did not lead to greater reductions in total sugar intake compared to consuming water [20].…”
Section: But What About Weight?mentioning
confidence: 99%
“…Recently, the WHO have suggested that their 2015 guidelines on sugar intake should be used to develop a strategy for reformulation of processed foods, such as those rich in free sugars [6]. However, it should be recognized that the replacement of sugar-sweetened products with sugar-reduced or artificially sweetened alternatives may be associated with compensatory responses in EI and/or energy expenditure (EE), which in turn may only lead to modest weight loss [1315]. Yet there are very limited data on the efficacy of using sugar-reformulated products on body weight, energy balance (EB) dynamics and the possibility of energy compensation [16].…”
Section: Introductionmentioning
confidence: 99%